Real-Time Differential Pricing Scheme for Active Consumers with Electric Vehicles. Issue 14 (27th August 2017) - Jhala, Kumarsinh; Natarajan, Balasubramaniam; Pahwa, Anil; Erickson, Larry
Abstract: Electric vehicles (EVs) are becoming increasingly popular because of their low operating costs. However, the anticipated increase in EV usage presents opportunities as well as challenges for utilities. This paper models EV charging behavior of active consumers who strategize their EV charging schedule to minimize the charging cost. The electric utility employs a temporal and spatially varying real-time pricing scheme that minimizes peak-to-average load ratio by influencing charging behavior of multiple active consumers. These active consumers decide their optimal charging strategy based on real-time electricity prices in order to minimize their EV charging cost. A model predictive control (MPC)-based optimal pricing scheme for electric utility and optimal charging strategy for active consumers is proposed. Effects of the proposed approach on load profile is verified using simulations.